The Impact of the One China Policy on Indonesia's Diplomatic Relations with Taiwan - Wahyudi, Sava Anisha (Universitas Sebelas Maret, 2021)
The One China Policy or commonly referred to as the One China Policy is China's policy which states that no more Chin countries may be recognized other than their own. In this case, another country referred to by China is Taiwan, which also claims to be a country that has original power over mainland China and claims to be an independent country, not under the control of the People's Republic of China. Indonesia is one of the countries that implements the implementation of the One China Policy so that it has a fairly large impact on diplomatic relations or cooperation between Indonesia and Taiwan.